(untitled) (Journal of Management and Social Sciences, 2024)
Abstract This paper explores the challenges and dynamics of development in Nigeria, particularly through the lens of capitalism and its accompanying socio-economic structures. By examining the historical and contemporary influences of capitalist values, the paper delves into how these forces shape educational institutions, labor markets, and national economic policies. It highlights the pervasive role of corruption within the capitalist framework and its implications for Nigeria’s development trajectory. Furthermore, the paper critiques the external impositions of development models by global institutions and advocates for a bottom-up approach to defining and addressing the country’s developmental needs. Through this analysis, the paper aims to provide a nuanced understanding of the complexities surrounding Nigeria’s quest for development and the need for a more indigenous and self-sustained approach to progress. Keywords Nigeria, development, capitalism, corruption, socio-economic structures